Long-term outcomes of catheter ablation of atrial fibrillation in dilated cardiomyopathy. (1st July 2015) - Zhao, Liang; Xu, Kai; Jiang, Weifeng; Zhou, Li; Wang, Yuanlong; Zhang, Xiaodong; Wu, Shaohui; Liu, Xu
Abstract: Objective: The long-term outcomes, efficacy and safety of catheter ablation in atrial fibrillation (AF) patients with dilated cardiomyopathy (DCM) have not been reported previously. Methods and results: Forty nine patients with AF (59% longstanding persistent AF, LSP-AF) and DCM were enrolled. Circumferential pulmonary vein ablation (CPVA, paroxysmal AF), bidirectional block of lines and disappearance of complex fractionated atrial electrograms (CFAEs, persistent and LSP-AF) were the endpoints of the index and repeat procedures. Cumulative success rate reached 49% (mean, 1.4 procedures) during the first year, and dropped to 38% at median follow-up of 45 months (range, 36–64 months) for multiple procedures (mean, 1.9 ± 0.8 [1–4]). Incidence of procedural complications was similar to that of conventional procedures. In multivariate analysis, LSP-AF (OR, 7.40 [95% CI, 1.42–38.34]; P = 0.017) and larger left ventricular end-diastolic diameter (OR, 1.24 [95% CI, 1.01–1.52]; P = 0.034) were significant independent predictors of recurrent atrial tachyarrhythmia (ATa). Compared with patients with ATa recurrence, those free from ATa had better New York Heart Association functional class, 6-minute walk distance and left ventricular ejection fraction during long-term follow-up compared with pre-ablation, but this improvement was not sustained beyond 3 years. Conclusion: In patients with DCM, current commonly used ablation strategies including CPVA, linear ablation and CFAE ablation are not associated with long-term AF treatment success up to five years. Freedom from ATa is associated with improved heart failure during but not beyond 3 years post ablation.